Aging impairs intermediate-term behavioral memory by disrupting the dorsal paired medial neuron memory trace - Tonoki, Ayako (National Academy of Sciences, 2012)
How the functional activity of the brain is altered during aging to cause age-related memory impairments is unknown. We used functional cellular imaging to monitor two different calcium-based memory traces that underlie olfactory classical conditioning in young and aged Drosophila. Functional imaging of neural activity in the processes of the dorsal paired medial (DPM) and mushroom body neurons revealed that the capacity to form an intermediate-term memory (ITM) trace in the DPM neurons after learning is lost with age, whereas the capacity to form a short-term memory trace in the α′/β′ mushroom body neurons remains unaffected by age. Stimulation of the DPM neurons by activation of a temperature-sensitive cation channel between acquisition and retrieval enhanced ITM in aged but not young flies. These data indicate that the functional state of the DPM neurons is selectively altered with age to cause an age-related impairment of ITM, and demonstrate that altering the excitability of DPM neurons can restore age-related memory impairments.